Patterns of synaptic activity in neural networks recorded by light emission from synaptolucins. - Miesenböck, G; Rothman, J (1997)
The emission of light, coupled to exocytosis, can in principle be utilized to monitor the activity of a large number of individual synapses simultaneously. To illustrate this concept, fusion proteins of Cypridina luciferase and synaptotagmin-I or VAMP-2/synaptobrevin (which we term "synaptolucins") were expressed in cultured hippocampal neurons with the help of viral vectors. Synaptolucins were targeted to synaptic vesicles and, upon exocytosis, formed light-emitting complexes with their cognate luciferin, which was added to the extracellular medium. Photon emissions required a depolarizing stimulus, occurred from regions with high synaptic density as ascertained by vital staining of recycling synaptic vesicles, and were sensitive to Ca2+ depletion and clostridial neurotoxins. The method can currently detect exocytosis of the readily releasable pool of synaptic vesicles at a hippocampal synapse, corresponding to about two dozen quanta, but has the potential for greater sensitivity.